Naloxone without the needle − systematic review of candidate routes for non-injectable naloxone for opioid overdose reversal. (1st June 2016) - Strang, John; McDonald, Rebecca; Alqurshi, Abdulmalik; Royall, Paul; Taylor, David; Forbes, Ben
Highlights: Deaths from opioid overdose can be prevented by prompt injection of the opiate antagonist naloxone. After 40 years of injection-based naloxone, a concentrated naloxone nasal spray is now approved. Systematic review finds 3 potential injection-free naloxone routes: nasal, sublingual & buccal. Alongside concentrated nasal naloxone, buccal may have distinct advantages as future product. Wider pre-provision of naloxone across the community is essential; all three routes warrant study. Abstract: Introduction: Deaths from opioid overdose can be prevented through administration of the antagonist naloxone, which has been licensed for injection since the 1970s. To support wider availability of naloxone in community settings, novel non-injectable naloxone formulations are being developed, suitable for emergency use by non-medical personnel. Objectives: 1) Identify candidate routes of injection-free naloxone administration potentially suitable for emergency overdose reversal; 2) consider pathways for developing and evaluating novel naloxone formulations. Methods: A three-stage analysis of candidate routes of administration was conducted: 1) assessment of all 112 routes of administration identified by FDA against exclusion criteria. 2) Scrutiny of empirical data for identified candidate routes, searching PubMed and WHO International Clinical Trials Registry Platform using search terms "naloxone AND [route of administration]". 3) Examination of routes for feasibility and against the inclusion criteria. Results: Only three routes of administration met inclusion criteria: nasal, sublingual and buccal. Products are currently in development and being studied. Pharmacokinetic data exist only for nasal naloxone, for which product development is more advanced, and one concentrated nasal spray was granted licence in the US in 2015. However, buccal naloxone may also be viable and may have different characteristics. Conclusion: After 40 years of injection-based naloxone treatment, non-injectable routes are finally being developed. Nasal naloxone has recently been approved and will soon be field-tested, buccal naloxone holds promise, and it is unclear what sublingual naloxone will contribute. Development and approval of reliable non-injectable formulations will facilitate wider naloxone provision across the community internationally.